A history of American literature 1950 to the present - Wagner-Martin, Linda (Chichester, West Sussex ; Malden, MA : Wiley Blackwell, 2013)
The History of American Literature from 1950 to the Present offers a comprehensive analysis of the wide range of literary works that extends into the 21st centuryCovers drama, poetry, fiction, non-fiction, memoirs, science fiction, and detective novelsFeatures discussion of American works within the context of such 21st-century issues as globalization, medicine, gender, education, and other topics.
Sexual Preferences and Social/Legal IssuesTheater of the 1990s; The Poem at the Turn into the Twenty-First Century; Story at the Turn into the Twenty-First Century; Southern Literature at the Turn into the Twenty-First Century; Chapter 7 The Twenty-First Century; The Story of 9/11 and Its Aftermath; Theater 2000-2010; Poetry 2000-2010; Memoir and Life-Writing 2000-2010; Fiction 2000-2010; References; Index.
Includes bibliographical references and index.
Print version record and CIP data provided by publisher.
Keywords: American literature -- 20th century -- History and criticism; American literature -- 21st century -- History and criticism; American literature -- 20th century -- History and criticism; LITERARY CRITICISM -- American -- General; American literature; 1900-2099; Electronic books; Criticism, interpretation, etc